(untitled) (Research, Society and Development, 2020)
The present study focuses on the distribution and abundance of the giant isopod community, based on specimens collected using the bottom shrimp trawling on the Amazon continental shelf during fishery surveys, at depths between 81 m and 626 m, conducted during the REVIZEE/Score-North Program between 1996 and 1998. The study area is located within the exclusive economic zone of Brazil, between the States of Amapá and Pará. In total, 170 specimens were collected, distributed in the two species Bathynomus giganteus (n = 49) and Bathynomus miyarei (n = 121), in which 54% of the material were collected in the northern and 46% in the southern sector of the study area. B. miyarei was considered to be the dominant species in both sectors, whereas B. giganteus was uncommon in the northern sector, but abundant in the southern sector. Both species preferred gravelly bottoms in the northern sector, and gravelly sand in the southern sector and were more abundant during the dry season in the northern sector, but during the rainy season in the southern sector. The smallest female B. giganteus was collected in the northern sector, and the largest in the southern sector, whereas both the largest and the smallest female B. miyarei were captured in the southern sector. All the male specimens collected in this study were captured in the northern sector.